2022
DOI: 10.3389/fpsyg.2022.1002399
|View full text |Cite
|
Sign up to set email alerts
|

How and when workplace ostracism influences employee deviant behavior: A self-determination theory perspective

Abstract: Drawing on self-determination theory, this study examines the relationship between workplace ostracism and deviant behavior by focusing on the mediating role of basic psychological needs and the moderating role of perceived inclusive climate. Findings based on the analysis of 247 valid survey samples suggest that (1) workplace ostracism has a significant positive impact on employees’ deviant behavior; (2) basic psychological needs mediate the relationship between workplace ostracism and employees’ deviant beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…However, leader favouritism, often seen as a negative form of leadership behaviour (Liang et al ., 2022), is yet to be examined. The research lacuna is telling as this phenomenon seems prevalent (Luo et al ., 2022), which can harm organisational effectiveness if not effectively managed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…However, leader favouritism, often seen as a negative form of leadership behaviour (Liang et al ., 2022), is yet to be examined. The research lacuna is telling as this phenomenon seems prevalent (Luo et al ., 2022), which can harm organisational effectiveness if not effectively managed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A survey conducted by the Workplace Bullying Institute in 2021 amongst 1,215 adult Americans found that nearly one-third (30%) said they directly experienced abusive conduct at work and 4% admitted that they had bullied others at work (Namie, 2021). Luo et al . (2022) reported that such a workplace phenomenon was also evident elsewhere.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2021), lower levels of turnover (Panicker and Sharma, 2020), less exhaustion (Behnke et al. , 2022) and fewer negative acts at work (Luo et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%